Analysis of the Implementation of the Realistic Mathematics Education Approach to Overcoming Mathematics Learning Difficulties in Grade IV Students at Madrasah Ibtidaiyah - Rizki Isma Wulandari; Siti Fatonah (Universitas Muhammadiyah Mataram, 2024)
The purpose of this study was to analyze the implementation of the realistic mathematics education (RME) approach to overcome mathematics learning difficulties in grade IV students at Madrasah Ibtidaiyah. Learning difficulties experienced by students of madrasah ibtidaiyah age on average are difficulties in understanding concepts, low arithmetic operation skills, and a lack of mathematical problem-solving skills in high grades. So teachers need to create contextual, relevant, and interesting learning through the RME approach. The method used in this research is a qualitative approach with a case study type. The informants in this study consisted of 7 informants, namely the principal, class teacher, and 5 students. Data collection techniques include observation of the real situation in the field, interviews by asking 25–38 questions of informants, and supporting documentation. Data analysis techniques in this study are data reduction, data presentation, and conclusions. The data validity technique uses source triangulation. The results of this study indicate that the implementation of the realistic mathematics education (RME) approach has gone well by utilizing objects in the students' daily environment, namely donuts, pebbles, pencils, and money. This has a positive impact on overcoming students' learning difficulties, as evidenced by the increase in students' daily test scores on number and measurement material from the class average of 72.85 to 80 and 81.90. Thus, it can be implied that the importance of teachers having the right approach and model in learning, especially using the Realistic Mathematics Education (RME) approach, lies in overcoming students' mathematics learning difficulties so that learning outcomes can be maximally realized. This approach is suitable for MI-aged children because, at the age of 7–11 years, students are not yet able to understand concrete material, so they need learning media or are associated with everyday life as an implementation of the RME approach.